Engineering Inhalable Therapeutic Particles: Conventional and Emerging Approaches - Aditi Negi; Shubham Nimbkar; Jeyan Arthur Moses (MDPI AG, 2023)
Respirable particles are integral to effective inhalable therapeutic ingredient delivery, demanding precise engineering for optimal lung deposition and therapeutic efficacy. This review describes different physicochemical properties and their role in determining the aerodynamic performance and therapeutic efficacy of dry powder formulations. Furthermore, advances in top-down and bottom-up techniques in particle preparation, highlighting their roles in tailoring particle properties and optimizing therapeutic outcomes, are also presented. Practices adopted for particle engineering during the past 100 years indicate a significant transition in research and commercial interest in the strategies used, with several innovative concepts coming into play in the past decade. Accordingly, this article highlights futuristic particle engineering approaches such as electrospraying, inkjet printing, thin film freeze drying, and supercritical processes, including their prospects and associated challenges. With such technologies, it is possible to reshape inhaled therapeutic ingredient delivery, optimizing therapeutic benefits and improving the quality of life for patients with respiratory diseases and beyond.